Implications of Kali–Hindon inter-stream aquifer water balance for groundwater management in western Uttar Pradesh - Mohammad Muqtada Ali Khan; Rashid Umar (2008)
The Kali–Hindon inter-stream region extends over an area of 395km2 within the Ganga–Yamuna interfluve. It is a fertile tract for sugarcane cultivation. Groundwater is a primary resource for irrigation and industrial purposes. In recent years, over-exploitation has resulted in an adverse impact on the groundwater regime. In this study, an attempt has been made to calculate a water balance for the Kali–Hindon inter-stream region. Various inflows and outflows to and from the aquifer have been calculated. The recharge due to rainfall and other recharge parameters such as horizontal inflow, irrigation return flow and canal seepage were also evaluated. Groundwater withdrawals, evaporation from the water table, discharge from the aquifer to rivers and horizontal subsurface outflows were also estimated. The results show that total recharge into the system is 148.72million cubic metres (Mcum), whereas the total discharge is 161.06 Mcum, leaving a deficit balance of −12.34Mcum. Similarly, the groundwater balance was evaluated for the successive four years. The result shows that the groundwater balance is highly sensitive to variation in rainfall followed by draft through pumpage. The depths to water level are shallow in the canal-irrigated northern part of the basin and deeper in the southern part. The pre-monsoon and post-monsoon water levels range from 4.6 to 17.7m below ground level (bgl) and from 3.5 to 16.5m bgl respectively. It is concluded that the groundwater may be pumped in the canal-irrigated northern part, while withdrawals may be restricted to the southern portion of the basin, where intense abstraction has led to rapidly falling water table levels.